DEVELOPMENT OF ELECTRONIC MODULE OF MATHEMATICS ON SEQUENCE SUBJECT MATTER FOR CLASS XI - Sonya Madyo Ratri; Aris Thobirin (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
This research is motivated by the lack of teaching materials in electronic modules to help students learn independently. This development research aims to develop, find out the feasibility, and know the students' response to the mathematics e-module subject matter for high school class XI students based on the curriculum 2013 using assessment from material experts, media Experts student responses. This research is development research with ADDIE (Analysis, Design, Development, Implementation, and Evaluation) models that produce products in the form of mathematics e-module subject matter sequence for high school students of class XI curriculum 2013 using Kvisoft Flipbook Maker Pro Software. Subjects in this study were material experts, media experts, and class XI students at SMA Negeri 1 Sewon Bantul and State Senior High School (SMA Negeri) 2 Ngaglik Sleman in the 2017/2018 Academic Year. The object of this study is the product of e-modules developed. This data collection technique is in the form of a questionnaire technique. The research data were obtained from questionnaires for media experts, material experts, and student responses. The data in this study were analyzed quantitatively and qualitatively to determine the feasibility of the e-module developed and to find out the students' response to the e-modules developed. This study succeeded in developing Mathematical e-module subject matter for high school students based on the curriculum 2013. From the expert material assessment results, an average score of 92.3 was obtained with eligible criteria. The media expert assessment obtained an average score of 104.3 with very feasible criteria. The assessment of student responses obtained an average score of 74.4 with good criteria. These results indicate that the mathematics e-module subject matter sequence for high school students in class XI based on the curriculum 2013 is appropriate for the classroom's learning process.